A CORRELATIONAL STUDY TO ASSESS THE RELATIONSHIP BETWEEN ACADEMIC STRESS AND LEVEL OF SELF-ESTEEM AMONG ADOLESCENTS IN SELECTED SETTINGS (Journal of Pharmaceutical Negative Results, 2023)
Background: Academic stress causes the poor attitudes toward school, failed classes, difficult relationships with teachers and lack of confidence in their academic work among adolescents.Aim of the study: Aim to assess the correlation between academic stress and self-esteem among adolescents.Methods: The corelational study was conducted with 40 adolescents (14-15 years) in government school. The convenience sampling technique was used to select the samples. Rosenberg self-esteem scale and academic stress scale used for data collection.Results: The mean score of academic stress was 46.4 with SD 2.17 and the mean score of self-esteem was 12.3 with SD 4.15. The calculated r value was r = -0.585, (P<0.01).Conclusion: The study has proved that there is a significant but, moderately negative correlation is found between academic stress and self-esteem among adolescents.